Comparison of noncycloplegic and cycloplegic autorefraction in categorizing refractive error data in children - Sankaridurg, Padmaja; He, Xiangui; Naduvilath, Thomas; Lv, Minzhi; Ho, Arthur; Smith, Earl; Erickson, Paul; Zhu, Jianfeng; Zou, Haidong; Xu, Xun (Acta ophthalmologica (Oxford, England), 2017)
Purpose To systematically analyse the differences between cycloplegic and noncycloplegic refractive errors (RE) in children and to determine if the predictive value of noncycloplegic RE in categorizing RE can be improved. Methods Random cluster sampling was used to select 6825 children aged 4–15 years. Autorefraction was performed under both noncycloplegic and cycloplegic (induced with 1% cyclopentolate drops) conditions. Paired differences between noncycloplegic and cycloplegic spherical equivalent (SE) RE were determined. A general linear model was developed to determine whether cycloplegic SE can be predicted using noncycloplegic SE, age and uncorrected visual acuity (UCVA). Results Compared to cycloplegia, noncycloplegia resulted in a more myopic SE (paired difference: −0.63 ± 0.65D, 95% CI: −0.612 to −0.65D, 6017 eligible right eyes) with greater differences observed in younger participants and in eyes with more hyperopic RE and smaller AL. Using raw noncycloplegic data resulted in only 61% of the eyes being correctly classified as myopic, emmetropic or hyperopic. Using age and uncorrected VA in the model, the association improved and 77% of the eyes were classified correctly. However, predicted cycloplegic SE continued to show large residual errors for low myopic to hyperopic RE. Applying the model to only those eyes with uncorrected VA <6/6 resulted in an improvement (R2 = 0. 93), with 80% of the eyes correctly classified. A higher VA cut‐off (i.e., ≤6/18) resulted in 97.5% of eyes classified correctly. Conclusion Noncycloplegic assessment of RE in children overestimates myopia and results in a high error rate for emmetropic and hyperopic RE. Adjusting for age and applying uncorrected VA cut‐offs to noncycloplegic assessments improves detection of myopic RE and may help in identifying myopic RE in situations where cycloplegia is not available but does not help in identifying the magnitude of refractive error and therefore is of limited value.